Long-term Mortality After Rapid Screening and Decolonization of Staphylococcus Aureus Carriers: Observational Follow-up Study of a Randomized, Placebo-controlled Trial. Issue 3 (March 2016) - Bode, Lonneke G. M.; Rijen, Miranda M. L. van; Wertheim, Heiman F. L.; Vandenbroucke-Grauls, Christina M. J. E.; Troelstra, Annet; Voss, Andreas; Verbrugh, Henri A.; Vos, Margreet C.; Kluytmans, Jan A. J. W.
Abstract : Objective: To identify patients who benefit most from Staphylococcus aureus screening and decolonization treatment upon admission. Background: S. aureus carriers are at increased risk of developing surgical-site infections with S. aureus . Previously, we demonstrated in a randomized, placebo-controlled trial (RCT) that these infections can largely be prevented by detection of carriage and decolonization treatment upon admission. In this study, we analyzed 1- and 3-year mortality rates in both treatment arms of the RCT to identify patient groups that should be targeted when implementing the screen-and-treat strategy. Methods: Three years after enrolment in the RCT, mortality dates of all surgical patients were checked. One- and 3-year mortality rates were calculated for all patients and for various subgroups. Results: After 3 years, 44 of 431 (10.2%) and 43 of 362 (11.9%) patients had died in the mupirocin/chlorhexidine and placebo groups, respectively. No significant differences in mortality rates were observed between the treatment groups or the subgroups according to type of surgery. In the subgroup of patients with clean procedures (382 cardiothoracic, 167 orthopedic, 61 vascular, and 56 other), mupirocin/chlorhexidine reduced 1-year mortality: 11 of 365 (3.0%) died in the mupirocin/chlorhexidine versus 21 of 301 (7.0%) in the placebo group [hazard ratio = 0.38 (95% CI: 0.18–0.81)]. Conclusions: Detection and decolonization of S. aureus carriage not only prevents S. aureus surgical-site infections but also reduces 1-year mortality in surgical patients undergoing clean procedures. Such patients with a high risk of developing S. aureus infections should therefore be the primary target when implementing the screen-and-treat strategy in clinical practice.